REGISTRO DE Tamarixia radiata (WATERSTON) (HYMENOPTERA: EULOPHIDAE) EM Diaphorina citri KUWAYAMA (HEMIPTERA: PSYLLIDAE) EM SÃO PAULO, BRASIL - Torres, Mariuxi L. Gómez; Nava, Dori E.; Gravena, Santin; Costa, Valmir A.; Parra, José R. P. (REVISTA DE AGRICULTURA, 2015)
REGISTRO DE Tamarixia radiata (WATERSTON) (HYMENOPTERA: EULOPHIDAE) EM Diaphorina citri KUWAYAMA (HEMIPTERA: PSYLLIDAE) EM SÃO PAULO, BRASIL